Critical behavior and magnetocaloric effect in C-implanted Fe93Zr7 amorphous films. (August 2020) - Charkaoui, A.; Moubah, R.; Bouhbou, M.; Lassri, H.; Elouafi, A.; Jönsson, P.E.
Abstract: We report on the effect of carbon ion-implantation on the critical behavior of Fe93 Zr7 amorphous films. Both the as-grown and carbon-implanted Fe93 Zr7 samples exhibit a second order ferromagnetic to paramagnetic transition. The critical exponents were investigated through different techniques such as modified-Arrott plot, the critical isotherm analysis and the Windom scaling relation. Analysis of the critical behavior was presented in terms of the magnetocaloric effect around TC . While there is a significant increase of the magnetization and TC upon C-implantation, the critical exponents were only slightly affected by implantation and were in line with those of the 3D-Heisenberg model.